2019
DOI: 10.3389/fendo.2019.00197
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc-α2-Glycoprotein Levels Were Decreased in Patients With Premature Coronary Artery Disease

Abstract: Objectives: To explore serum zinc-α2-glycoprotein (ZAG) changes in patients with or without premature coronary artery disease (PCAD) and its association with several cardiovascular risk factors. Methods: A total of 3,364 patients who were undergone coronary angiography in Peking Union Medical College Hospital were screened. According to the degree of coronary artery stenosis, the number of 364 patients with PCAD (age <55 years in males and <65 years in females) and 126 age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
3
15
0
Order By: Relevance
“…Recent clinical studies also found that serum ZAG levels were significantly lower in overweight/obese patients and were negatively correlated with BMI, waist circumstance, hip circumference, and fat mass [21,22]. Beyond these observations, accumulating evidence revealed the close relationship between serum ZAG levels and various cardiometabolic risk factors, including cigarette smoking [26], dyslipidemia [27], hypertension [25], T2DM [23,24], and metabolic syndrome [14] and our recently published paper in Chinese population [30] found the significant lower serum ZAG levels in PCAD patients (males <55y, females <65y) in comparison to the controls. Our present study further extended the available data in an elderly population and firstly found that serum ZAG levels were significantly lower in elderly CAD/NCAD patients from Chinese population.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Recent clinical studies also found that serum ZAG levels were significantly lower in overweight/obese patients and were negatively correlated with BMI, waist circumstance, hip circumference, and fat mass [21,22]. Beyond these observations, accumulating evidence revealed the close relationship between serum ZAG levels and various cardiometabolic risk factors, including cigarette smoking [26], dyslipidemia [27], hypertension [25], T2DM [23,24], and metabolic syndrome [14] and our recently published paper in Chinese population [30] found the significant lower serum ZAG levels in PCAD patients (males <55y, females <65y) in comparison to the controls. Our present study further extended the available data in an elderly population and firstly found that serum ZAG levels were significantly lower in elderly CAD/NCAD patients from Chinese population.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, our recently published paper in PCAD patients also demonstrated that subjects with low tertile ZAG levels have higher probability of PCAD/NPCAD than those with high ZAG tertile levels [30]. Even after adjusting for other confounders, this phenomenon still existed [30]. In this respect, ZAG was indicated International Journal of Endocrinology as a protective factor for CAD/NCAD, not only in the middleaged population, but also in an elderly population, and ZAG may be a candidate biomarker of the diagnosis of CAD/NCAD.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations